Lipid peroxidation inhibition by ethanolic extract and fractions from Rhamnus sphaerosperma var. pubescens (Reissek) M.C. Johnst. (Rhamnaceae) - Thais Fernanda Moreira; Daniella Maria Soares de Oliveira; Maria Fernanda Cordeiro Arruda; Beatriz Cristina Konopatzki Hirota; Ana Luisa Lacava Lordello; Patricia Maria Stuelp Campelo; Marilis Dallarmi Miguel; Obdulio Gomes Miguel (International Journal of Phytomedicine, 2013)
Rhamnus sphaerosperma var. pubescens is a species native to Brazil, found in the southern region, and still there is no data in the literature about biological activities of this plant. Therefore, the aims of this study were to verify the antioxidant activity and determine the ability to inhibit lipid peroxidation of crude ethanolic extract and it fractions hexane, chloroform and ethyl acetate of the stem. The total antioxidant activity was evaluated by phosphomolybdenum complex method. And the ability to inhibit lipid peroxidation was evaluated, in vitro and in vivo experiments, by quantification of thiobarbituric acid reactive species formed from peroxidation induced. The in vitro test about lipoperoxidation, were used lipids obtained from egg yolk. And, for in vivo assay, the peroxidation was determined only for crude extract, using stomachs of female rats injured by administration of absolute ethanol. The samples of Rhamnus sphaerosperma var. pubescens demonstrated an important antioxidant capacity. In the phosphomolybdenum complex method, the chloroform fraction (86.4%) and ethyl acetate fraction (96.2%) showed the best activity than crude extract. For the in vitro induced lipid peroxidation, the chloroform (63.3%) and hexane (59.7%) fractions demonstrated high capacity in prevention of lipid oxidation. The crude extract showed effectiveness in both methods, and was used in the verification of inhibition of lipid peroxidation in vivo. In this test, the lesser dose tested, 20 mg/Kg, showed better effectiveness in inhibiting lipid oxidation, with reduction of 56.9%. Furthermore, was possible identify the stigmasterol and sitosterol as compounds of this plant. Rhamnus sphaerosperma var. pubescens stem possess potential antioxidant activity, reducing lipid peroxidation tested by in vitro and in vivo methods.